Chair's note: working around the crisis in Libya. (25th September 2017) - Atkinson, David
Abstract: This is the first in a series of Chair's notes in Libyan Studies . We hope that future notes will address easier topics and more straightforward success, but for now we think it is important to communicate what we are doing given the difficult circumstances of Libya today. We trust that this report is useful, and we welcome any feedback. Abstract : هذه هي الأولى من مجموعة ملاحظات رئيس جمعية الدراسات الليبية. نأمل بأن تتناول الملاحظات اللاحقة موضوعات أسهل وأكثر نجاحا ، ولكن في الوقت الحالي نعتقد بأنه من المهم أن نتواصل معكم ونطلعكم على ما نقوم به في ظل الظروف الصعبة في ليبيا اليوم . ونحن على ثقة من أن هذا التقريرسيكون مفيداً، كما اننا نرحب دائمأ بتعليقاتكم وآرائكم.